LAW ASPECT IN TREATING ILLEGAL MINING CASE OF MINERAL C IN PATI REGENCY - S Suyoto; Dwiyana Achmad Hartanto (Jurnal Dinamika Hukum, 2018)
The research entitled "Law Aspect in Handling Illegal Mining Case of Mineral C in Pati Regency" is motivated by the increasing illegal mining of mineral C. It causes environmental damage, air pollution, licensing violation and tax. The research focus is limited to: (1) What are the influencing factors of illegal mining of mineral C in Sourthern Kendeng and Northern Kendeng mountains in Pati regency? (2) How to treat illegal mining case of mineral C in illegal areas of Southern Kendeng Mountain Area and Northern Kendeng Mountains in Pati Regency ? It applies sociological juridical approach. The results of the research showed: (1) Factors affecting illegal mining of mineral C in illegal areas of Southern Kendeng Mountain and Northern Kendeng Mountains include legal culture, legal structure and legal substance; (2) The treatment of illegal mining cases in the Southern Kendeng Mountains Area and the Northern Kendeng Mountains are conducted both penal and non penal.Keywords: Treatment, Mineral C, Illegal, Pati Regency